2022
DOI: 10.3390/microorganisms10030656
|View full text |Cite
|
Sign up to set email alerts
|

Short-Term Exposure to Thermophilic Temperatures Facilitates CO Uptake by Thermophiles Maintained under Predominantly Mesophilic Conditions

Abstract: Three phylogenetically and phenotypically distinct CO-oxidizing thermophiles (Alicyclobacillus macrosporangiidus CPP55 (Firmicutes), Meiothermus ruber PS4 (Deinococcus-Thermus) and Thermogemmatispora carboxidovorans PM5T (Chloroflexi)) and one CO-oxidizing mesophile (Paraburkholderia paradisi WAT (Betaproteobacteria)) isolated from volcanic soils were used to assess growth responses and CO uptake rates during incubations with constant temperatures (25 °C and 55 °C) and during multi-day incubations with a tempe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 42 publications
0
1
0
Order By: Relevance
“…The sampling carried out at the level of the thermal spring of Ouled Tebben allowed the isolation of only eight bacterial strains, five of which were cellulase positive, and the presence of a reduced bacterial population is explained by the high temperature of the thermal waters. These natural high-temperature environments will certainly influence the resident microbial flora; the microorganisms able to grow and survive in these environments where the temperature exceeds 50 • C are thermotolerant or thermophilic [20]. A similar study demonstrated that only 16% of the bacteria isolated from the hot springs of western Algeria have cellulases; this type of unexploited biotope could constitute a promising source of thermophilic enzymes of great industrial importance [21].…”
Section: Discussionmentioning
confidence: 98%
“…The sampling carried out at the level of the thermal spring of Ouled Tebben allowed the isolation of only eight bacterial strains, five of which were cellulase positive, and the presence of a reduced bacterial population is explained by the high temperature of the thermal waters. These natural high-temperature environments will certainly influence the resident microbial flora; the microorganisms able to grow and survive in these environments where the temperature exceeds 50 • C are thermotolerant or thermophilic [20]. A similar study demonstrated that only 16% of the bacteria isolated from the hot springs of western Algeria have cellulases; this type of unexploited biotope could constitute a promising source of thermophilic enzymes of great industrial importance [21].…”
Section: Discussionmentioning
confidence: 98%